Crowdsourcing ideas for public investment: the experience of youth participatory budgeting in Portugal - Bernardino, Susana (2020)
Participatory budgeting is a particular case of crowdsourcing that involves the participation of citizens in the political decision-making process regarding the distribution of a small part of the public budget among projects that were presented and voted by young citizens for public investment. The objective of the paper is to assess the content and results of the projects presented by young citizens in a participatory budgeting process that took place in 2017 in Portugal. Through the analysis of a database of 167 projects, this chapter aims to: (i) understand the characteristics of the projects presented through this specific public crowdsourcing platform; (ii) to study the profile of the youth participants; and (iii) to analyse the voting results. The results show that the projects were developed under the domain of different thematic areas, and most of them intend to be implemented at a regional or national level. The projects proposed in the crowdsourcing platform benefit both littoral and inner territories and involved an average budget around 28.700 euros, ranging from a minimum of 200 euros to the maximum allowed in the application (75.000 euros). With respect to the proponents’ profile, we observe that male youth citizens were slightly more active in the generation of ideas for projects than female, whereas the applications were mostly made individually or by teams composed of a unique gender type. Concerning the voting results, we observe that there is an intense concentration of votes in a few projects. Projects developed within the scope of inclusive sports, and environmental sustainability gathered more votes, as well as those that have a regional or multi-regional character or intend simultaneously to benefit both coastal and interior regions.